Transcriptional Analysis of L-Methionine Catabolism in the Cheese-Ripening Yeast Yarrowia lipolytica in Relation to Volatile Sulfur Compound Biosynthesis - Cholet, Orianne; Hénaut, Alain; Hébert, Agnès; Bonnarme, Pascal (Applied and Environmental Microbiology, 2008)
Yarrowia lipolytica is one of the yeasts most frequently isolated from the surface of ripened cheeses. In previous work, it has been shown that this yeast is able to convert L-methionine into various volatile sulfur compounds (VSCs) that may contribute to the typical flavors of several cheeses. In the present study, we show that Y. lipolytica does not assimilate lactate in the presence of L-methionine in a cheeselike medium. Nineteen presumptive genes associated with L-methionine catabolism or pyruvate metabolism in Y. lipolytica were transcriptionally studied in relation to L-methionine degradation. The expression levels of the YlARO8 (YALI0E20977g), YlBAT1 (YALI0D01265g), and YlBAT2 (YALI0F19910g) genes (confirmed by real-time PCR experiments) were found to be strongly up-regulated by L-methionine, and a greater variety and larger amounts of VSCs, such as methanethiol and its autooxidation products (dimethyl disulfide and dimethyl trisulfide), were released in the medium when Y. lipolytica was grown in the presence of a high concentration of L-methionine. In contrast, other genes related to pyruvate metabolism were found to be down-regulated in the presence of L-methionine; two exceptions were the YlPDB1 (YALI0E27005g) and YlPDC6 (YALI0D06930g) genes, which encode a pyruvate dehydrogenase and a pyruvate decarboxylase, respectively. Both transcriptional and biochemical results corroborate the view that transamination is the first step of the enzymatic conversion of L-methionine to VSCs in Y. lipolytica and that the YlARO8, YlBAT1, and YlBAT2 genes could play a key role in this process.